Conflicting Anthropologies in the Christological Discourse at the End of Late Antiquity: The Case of Leontius of Jerusalem's Nestorian Adversary - Krausmüller, Dirk (The journal of theological studies, 2005)
In his treatise Contra Nestorianos Leontius of Jerusalem reproduces excerpts from a Nestorian treatise which contend that the Chalcedonian understanding of the incarnation as a composition subjects Christ's divinity to universal ‘laws of compound beings’. These ‘laws’ are illustrated with the human being as a compound of the interdependent parts body and soul. In chapter 51 the author contrasts the belief in a ‘sleep of the soul’ that concurs with this monistic anthropology with the concept of a sentient afterlife which is based on a dualistic anthropology. The former position is presented as scriptural and rational while the alternative is denounced as a Manichaean myth. To support this claim the author creates a nexus between sentient afterlife and outlawed pre-existence whose proponents, the Origenists, had also been deemed non-Christian and irrational. Thus he can build on an existing anti-Origenist consensus and insinuate that he merely continues the cleansing of Christianity. Comparison with Philoponus’ Arbiter reveals the function of this polemic within the Christological debate: the Nestorian exploits similarities between the use of the anthropological paradigm by Nestorians and by ‘neo’-Chalcedonians and an anthropological controversy that pitted mainstream Christians against Origenists in order to denigrate his opponents as crypto-pagans.